2013
DOI: 10.1016/j.resourpol.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Is the convenience yield a good indicator of a commodity's supply risk?

Abstract: a b s t r a c tA strong increase in the demand for some commodities over the last decade will have a major impact on their future supply situation. Of increasing importance, therefore, is an assessment of a commodity's criticality, and especially its supply risk, by appropriate indicators. The literature has proposed numerous indicators of the supply risk. Here, we use the convenience yield of commodity futures as a supply risk indicator to address some of the major shortcomings of existing indicators, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Instead of assuming arbitrary values for the convenience yield, the (average) ones yielded by Heaney ()'s methodology for the full sample are used. In turn storage cost annualized rates are computed on the basis of LME warehousing rents, by following Stepanek, Walter, and Rathgeber ()'s procedure.…”
Section: Extensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead of assuming arbitrary values for the convenience yield, the (average) ones yielded by Heaney ()'s methodology for the full sample are used. In turn storage cost annualized rates are computed on the basis of LME warehousing rents, by following Stepanek, Walter, and Rathgeber ()'s procedure.…”
Section: Extensionsmentioning
confidence: 99%
“…The existence of feedback‐effects between spot and futures prices has been extensively studied in the extant literature, as documented by the survey article by Chow, McAleer, and Sequeira (). More recent contributions in the area are Brooks, Rew, and Ritson (), Pindyck (), Heaney (, , ), Watkins and McAleer (), Tilton, Humphreys, and Radetzki (), Stepanek, Walter, and Rathgeber (), and Gulley and Tilton (), among others…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous research has mainly focused on the use of the convenience yield as an indicator of supply shortage (e. g., Stepanek et al, 2013;Omura, Todorova, Li, & Chung, 2015), but it has neglected supply and demand interactions. Future research questions include studying metal price determination on the basis of fundamental factors, such as consumption, secondary (scrap) and mine production.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to link explicitly metal demand and supply to futures markets dynamics. A previous study in this line of research is Stepanek, Walter, and Rathgeber (2013), who focused on supply risk and concluded that the convenience yield had predictive power with respect to inventory/turnover and future spot prices. 4 This article is organized as follows.…”
Section: Introductionmentioning
confidence: 99%